Effects of a competition of mountain biking on the state of hydration in amateur cyclists - Cragnulini, F.; Fantuzzi, G. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
The purpose of this study was to assess the changes in the state of hydration in amateur cyclists of the discipline mountain biking (Rally) during a race of one day. Method: PRE and POST urine samples were obtained, in 13 amateur cyclists of this discipline, and urine specific gravity (USG) was analyzed by refractometer. Change in body mass was also registered and the volume of liquid ingested ad libitum during the competition was controlled. Results: The average pre-competition USG was 1034,33 ±6,8 and post-competition 1034 ± 6,6. The loss of body mass was 2.6 ± 0.7% and the average sweating rate was 707,5 ml/h ± 277,9. Conclusions: The results obtained indicate that the cyclists evaluated began and ended the competition in a severe dehydration state (i.e., USG> 1.020). However, despite starting in state of dehydration and having liquid and solid supplies ad libitum, the cyclists experienced a body mass loss higher than 2% during the competitive event.